Temperature measurement and control system for transtibial prostheses: Single subject clinical evaluation. Issue 3 (27th May 2018) - Ghoseiri, Kamiar; Zheng, Yong Ping; Leung, Aaron K.L.; Rahgozar, Mehdi; Aminian, Gholamreza; Masoumi, Mehdi; Safari, Mohammad Reza
ABSTRACT: The snug fit of a prosthetic socket over the residual limb can disturb thermal balance and put skin integrity in jeopardy by providing an unpleasant and infectious environment. The prototype of a temperature measurement and control (TM&C) system was previously introduced to resolve thermal problems related to prostheses. This study evaluates its clinical application in a setting with reversal, single subject design. The TM&C system was installed on a fabricated prosthetic socket of a man with unilateral transtibial amputation. Skin temperature of the residual limb without prosthesis at baseline and with prosthesis during rest and walking was evaluated. The thermal sense and thermal comfort of the participant were also evaluated. The results showed different skin temperature around the residual limb with a temperature decrease tendency from proximal to distal. The TM&C system decreased skin temperature rise after prosthesis wearing. The same situation occurred during walking, but the thermal power of the TM&C system was insufficient to overcome heat build-up in some regions of the residual limb. The participant reported no significant change of thermal sense and thermal comfort. Further investigations are warranted to examine thermography pattern of the residual limb, thermal sense, and thermal comfort in people with amputation.